Simulation study of accelerator based quasi-mono-energetic epithermal neutron beams for BNCT. (January 2016) - Adib, M.; Habib, N.; Bashter, I.I.; El-Mesiry, M.S.; Mansy, M.S.
Abstract: Filtered neutron techniques were applied to produce quasi-mono-energetic neutron beams in the energy range of 1.5–7.5 keV at the accelerator port using the generated neutron spectrum from a Li (p, n) Be reaction. A simulation study was performed to characterize the filter components and transmitted beam lines. The feature of the filtered beams is detailed in terms of optimal thickness of the primary and additive components. A computer code named "QMNB-AS" was developed to carry out the required calculations. The filtered neutron beams had high purity and intensity with low contamination from the accompanying thermal, fast neutrons and γ-rays. Highlights: Epithermal neutron beams used in BNCT. Quasi-monoenergetic neutron beams in energy range from (1.5–7.5) keV. Interference between the resonance and the potential scattering amplitudes.